(3GdefXheI GdLdLdhJjIs - (3GdgGTej, GdbQTj, CHh GdMSf, Ydj Hf CHj WGdH Hf YHO GdeWdH, J (B40 (3gs
(3ChdgG (B:s
(3HOCJ HHSe Gddg QhMj Hg GgJOJ (B*** (3Edi cTa CSQGQ HHGWfg GfWhJs
(3BNQgG (B:s
(3hNP HjOj Ef GdCehQ bO GdJhJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 295s
(3eYLe GdeDdajf(B: 2 / 452s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs